Peran Pilar Demokrasi dalam Meningkatkan Ketahanan Nasional di Tengah Tantangan Globalisasi - Zaky Umar Rachman (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
This research discusses the role of the pillars of democracy, namely the rule of law, community participation, and government transparency, in building Indonesia's national resilience in the era of globalisation. Using a qualitative approach based on literature analysis, this study finds that the rule of law supports social stability through the enforcement of justice, community participation strengthens government legitimacy, and transparency increases accountability and public trust. Global challenges such as economic dependency and radical ideologies require strengthening democracy through legal reform, political education, and administrative digitalisation. With this strategy, Indonesia can face the dynamics of globalisation while maintaining its national stability and sovereignty.